Efeito de sistemas de cultivo e de fungicidas sobre a podridão gomosa (Didymella bryoniae) em meloeiro cultivado em ambiente protegido - Penharbel, Marcelo Paes (2011)
The muskmelon belongs to the Cucurbitaceae family, is an agronomic crop that has great importance in the volume of fruit exported by Brazil. In this context, the gummy stem blight caused by Didymella bryoniae has been the most important disease for the muskmelons in greenhouse with damage reaching up to 100%. The most frequent symptoms correspond to tipping and cancer, with gum exudation on the stem. D. bryoniae survives in crop residues, soil and infested seeds. This pathogen is difficult to control after its establishment in the field and the use of registered chemicals have been shown ineffective for the control of gummy stem blight and not yet obtained any melon cultivar resistant under field conditions. So, one of the strategies that could be used as exclusion would be to prevent the entry of pathogen in the cultivated area, mainly by the use of healthy seeds or treatment of seeds, or application of fungicides in plants. For this it is important to evaluate new fungicides to seed treatment and spraying of seedlings and regular spraying in the field, to apply new strategies to improve the information management of the disease. Other strategies can be employed associated with chemical control, among these strategies can be emphasized cropping systems that provide conditions less favorable to gummy stem blight as hydroponic cultivation and / or mulching. Given the above, the present study was to evaluate the intensity of gummy stem blight in different cultivation systems in greenhouse muskmelon, alone or in combination with the use of fungicides at different stages of crop development. The work was composed of three chapters: Chapter I, we studied the disease control using three cropping systems, soil, mulching and hydroponic with and without the regular application of fungicides in culture. In Chapter II, we studied the efficiency of the initial control of the disease and during the crop cycle employing spraying of seedlings in the pre-planting and regular spraying in established culture in the field in conventional crop on soil. In Chapter III, we studied the application and simple formulation mixture of epoxiconazole + pyraclostrobin in seed treatment, spraying of seedlings and spraying in the field on hydroponics conditions.